Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Answer:
y = -⅔x + 2
Step-by-step explanation:
Given the linear equation, 2(x-3) + 3y = 0, for which we must transform into its slope-intercept form, y = mx + b:
First, distribute 2 into the parenthesis:
2(x-3) + 3y = 0
2x - 6 + 3y = 0
Next, subtract both sides by 2x:
2x - 2x - 6 + 3y = - 2x
Then, add 6 to both sides of the equation:
- 6 + 6 + 3y = - 2x + 6
3y = -2x + 6
Lastly, divide both sides by 3 to isolate y:
[tex]\displaystyle\mathsf{\frac{3y}{3}\:=\:\frac{-2x\:+\:6}{3}}[/tex]
y = - ⅔x + 2 ⇒ This is the slope-intercept form.
If there’s something with my handwriting you don’t understand let me know… I was writing fast lol.
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.